Komunikasi Internal Department Front Office Di Hotel Moxy Bandung - Superiwratni superwiratni; Eres Prmono (JURNAL PARIWISATA VOKASI, 2022)
In this study, it focused on communication between superiors and subordinates in the Moxcy Hotel Front Office where good communication is very important to achieve a goal in the front office to produce employee performance and create a good hotel image. Hotel Moxy Bandung also implements downward vertical communication from the superior to the supervisor of the front office to the receptionist. The delivery of information or messages delivered from the front office boss to the receptionist in the form of assigning tasks, explanations about tasks and so on. The benefit of establishing good horizontal communication is that employees can improve the coordination of tasks assigned from superiors so that employees can work together to perform tasks that have been given by superiors, not only that employees can solve problems together to find solutions to the problem. This study used a likert scale by distributing questionnaires.